Religious freedom in Islam: the fate of a universal human right in the Muslim world today - Philpott, Daniel (Oxford scholarship online, 2019)
Is Islam hospitable to religious freedom? The question is at the heart of a public controversy over Islam that has raged in the West over the past decade-and-a-half. Religious freedom is important because it promotes democracy and peace and reduces ills like civil war, terrorism, and violence. Religious freedom also is simply a matter of justice-not an exclusively Western principle but rather a universal human right rooted in human nature. The heart of the text confronts the question of Islam and religious freedom through an empirical examination of Muslim-majority countries. From a satellite view, looking at these countries in the aggregate, the work finds that the Muslim world is far less free than the rest of the world.